EGNOS based virtual reference stations - Soares, Manuel Gonçalves (2008)
We propose the use of the European Geostationary Navigation Overlay Service (EGNOS) data - real time on line data provided by SISNeT - to develop Virtual Reference Stations and, thus, increase the quality of the Position, Velocity an Time (PVT) solution of receivers unable to interface directly with EGNOS. A Virtual Reference Station (VRS) is a concept where the existence of a differential reference station located near a mobile rover is simulated by software in order to increase the accuracy of the PVT solution of the mobile GNSS receiver.